KONSTRUKSI PEMBINGKAIAN VISUAL EDHY PRABOWO DALAM KASUS KORUPSI BENUR PADA ILUSTRASI SAMPUL MAJALAH DAN KORAN TEMPO - Ben Isa Muhammad; Umaimah Wahid (Metacommunication: Journal of Communication Studies, 2021)
Tempo publications between 23-30 November 2020, raised the issue of corruption in the export of lobster seeds (Bahasa: Benur). Tempo tried to present the figure of  Edhy Prabowo on several covers by using a variety of intriguing visual illustrations, surreal depiction and signs. There is an effort to frame the figure of Edhy Prabowo in the case of fry export, visually as well as textually in the article contents . This study uses a qualitative approach with framing analysis method. The Gamson-Modigliani framing analysis model is used to analyze the main cover line texts contained in the cover illustration. To analyze Visual Framing, Rodriguez-Dimitrova's 4 levels of visual framing model was used. Of the 4 covers studied, Tempo seems to be trying to present its main subject in a denotative way, by using Edhy Prabowo's caricature and fry visuals appeared as the image focus. Abstract subjects such as 'export' are presented connotatively through symbols. Edhy Prabowo's visual framing process using illustrations on the cover of Tempo media looks like a visual story highlights, depicting one chapter after another. First act, Edhy Prabowo as an intellectual actor who has power in the fry export game. Second act, Edhy Prabowo fell into his own toy. Third act, flashback of the scheming of new rules for fry export. The fourth act, disclosure of the characters behind the scenes.